Common bottlenose dolphins Tursiops truncatus of Pacific South America, a synoptic review of population identification data - Van Waerebeek, Koen (2017)
Variation in dorsal fin morphology was assessed in five bottlenose dolphin (Tursiops truncatus) populations from the Southeast Pacific. We hypothesized that habitat specialization between coastal and offshore ecotypes led to differences in dorsal fin morphology. Photographs and direct measurements of dorsal fins were used to calculate three indexes: height/length base (h/b), width at half height/length base (a/b) and overhang of the dorsal fin tip/length base (falcateness) (s/b). The sample included 163 individuals (129 coastal and 34 offshore) from Ecuador, 60 individuals (9 coastal and 51 offshore) from Peru and 25 individuals of an inshore form from northcentral Chile (Pod-R). Values were logarithmically transformed to allow one-way ANOVAs and t-tests. Ontogenetic variation was found in coastal dolphins from Ecuador, with indices significantly different among age/classes. All indices were higher in juveniles and calves, suggesting a stronger (allometric) growth of the dorsal fin base (b) than in the upper parts of the fin. Hence only adults and subadults were considered in further analysis. Statistically significant differences were found in h/b and a/b indices between coastal specimens from Ecuador and Peru, and between offshore specimens from Ecuador and Peru, and Pod-R. Offshore and Pod-R data were pooled and compared with coastal specimens from Ecuador and Peru; significant differences were found in indices h/b and s/b. Offshore dorsal fins are relatively higher than coastal fins. However the most consistent and visible difference between ecotypes was the strong falcateness (high s/b) in the offshore forms vs. a more triangular shape (low s/b) in coastal forms. Except one outlier, all other cases could be correctly classified through ocular inspection by experienced observers. Chile's Pod-R represents a unique case of an inshore form with strong falcateness, a typical offshore trait. Ecuadorian offshore form showed highest relative dorsal fin height (h/b), followed by Peruvian coastal form, Pod-R, Peruvian offshore and, lowest, Ecuadorian coastal. Relative fin width at mid-height (a/b) was widest in Peruvian coastal stock, followed by Ecuadorian offshore, Peruvian offshore, Ecuadorian coastal and narrowest in Chilean Pod-R. The latter had also the highest falcateness index of all groups, consistent with their extremely falcate dorsal fins. Extreme values for two of three indices agree with marked molecular differences between Pod-R dolphins and Peruvian dolphins and, to a lesser degree, Chilean offshore. Pod-R may represent a recent radiation into the coastal environment from offshore ancestors, a sort of 'transitional form'. High falcateness may be retained due to particularities of the local environment, e.g. fairly deep water.